Different parasite faunas in sympatric populations of sister hedgehog species in a secondary contact zone - Pfäffle, Miriam; Černá Bolfíková, Barbora; Hulva, Pavel; Petney, Trevor (PloS one, 2014)
Providing descriptive data on parasite diversity and load in sister species is a first step in addressing the role of host-parasite coevolution in the speciation process. In this study we compare the parasite faunas of the closely related hedgehog species Erinaceus europaeus and E. roumanicus from the Czech Republic where both occur in limited sympatry. We examined 109 hedgehogs from 21 localities within this secondary contact zone. Three species of ectoparasites and nine species of endoparasites were recorded. Significantly higher abundances and prevalences were found for Capillaria spp. and Brachylaemus erinacei in E. europaeus compared to E. roumanicus and higher mean infection rates and prevalences for Hymenolepis erinacei, Physaloptera clausa and Nephridiorhynchus major in E. roumanicus compared to E. europaeus. Divergence in the composition of the parasite fauna, except for Capillaria spp., which seem to be very unspecific, may be related to the complicated demography of their hosts connected with Pleistocene climate oscillations and consequent range dynamics. The fact that all parasite species with different abundances in E. europaeus and E. roumanicus belong to intestinal forms indicates a possible diversification of trophic niches between both sister hedgehog species.
Keywords: fylogeografie; Biological Evolution; sympatrie; Animals; Hedgehogs; Helminthiasis, Animal; Sympatry; Phylogeography; zvířata; biologická evoluce; ježkovití; helmintózy zvířat